Opinion 2437: Trochus (Osilinus?) capillaceus Philippi, 1849 (currently Cantharidus capillaceus; Mollusca, Gastropoda, Trochoidea): precedence given over Trochus episcopus Hombron & Jacquinot, 1848 - ICZN (Bulletin of Zoological Nomenclature, 2019)
The International Commission on Zoological Nomenclature has conserved the usage of the specific name of Trochus (Osilinus?) capillaceus Philippi, 1849 (currently Cantharidus capillaceus) by giving it precedence over its senior subjective synonym Trochus episcopus Hombron & Jacquinot, 1848.
Keywords: Nomenclature; taxonomy; Mollusca; Gastropoda; Trochoidea; Cantharidus; Micrelenchus; Photinula; Trochus; Trochus capillaceus; Trochus episcopus; New Zealand